The “baby steps” in mainstreaming sustainable public procurement in Ghana: A “double‐agency” perspective - Adjei-Bamfo, P.; Maloreh-Nyamekye, T. (Journal of Public Affairs, 2019)
The emerging literature on public procurement policy suggests that public procurement may be leveraged to advance several public policy agenda. Hence, many countries have reformed their public procurement process towards social and environmental outcomes termed sustainable public procurement. These reforms have often been launched in response to international initiatives such as the global 10‐year framework for action on sustainable consumption and production by the Johannesburg implementation plan in 2002 and the Sustainable Development Goals. Yet, empirical evidence on the drivers and benefits of SPP in developing countries is still scarce. This gap is addressed with a qualitative case study of six public sector institutions in Ghana. On the basis of elite interviews, this paper highlights barriers to mainstreaming SPP in Ghana's public sector. We further advance the scanty principal–agency literature by establishing a double‐agency relationship in the context of SPP, which depicts limited agency cases where principals lack the capacity to defend their own interests.